2021
DOI: 10.3390/toxins13110795
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dietary Exposure to Ochratoxin A in Lebanese Students and Its Urinary Biomarker Analysis

Abstract: The present study investigated the dietary and urinary OTA occurrence among 44 Lebanese children. Relying on HPLC-FLD analysis, OTA was found in all the urine samples and in 46.5% and 25% of the 24 h duplicate diet and dinner samples, respectively. The means of OTA levels in positive samples were 0.32 ± 0.1 ng/g in 24 h diet, 0.32 ± 0.18 ng/g in dinner and 0.022 ± 0.012 ng/mL in urines. These values corresponded to margin of exposure (MOE) means of 7907 ± 5922 (neoplastic) and 2579 ± 1932 (non-neoplastic) calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…The dietary exposure to OTA for regular consumption was calculated, and is shown in Table 5 . The average total dietary intake of OTA was 1.345 ng/kg bw/day from thyme-based products, which was similar to another study conducted in Lebanon testing a 24 h diet showing a mean exposure of 1.4 ng/kg bw/day from the 24 h diet [ 26 ]. However, other studies in Lebanon reported higher exposures of 4.28 ng/kg bw/day [ 8 ] and 7.60 ng/kg bw/day [ 25 ].…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…The dietary exposure to OTA for regular consumption was calculated, and is shown in Table 5 . The average total dietary intake of OTA was 1.345 ng/kg bw/day from thyme-based products, which was similar to another study conducted in Lebanon testing a 24 h diet showing a mean exposure of 1.4 ng/kg bw/day from the 24 h diet [ 26 ]. However, other studies in Lebanon reported higher exposures of 4.28 ng/kg bw/day [ 8 ] and 7.60 ng/kg bw/day [ 25 ].…”
Section: Resultssupporting
confidence: 80%
“…For the dried herbs category, only thyme regular mix exceeded the acceptable limit according to the Lebanese standards, with a concentration of 4.83 µg/kg. Other studies conducted in Lebanon reported higher OTA concentrations of 9.13 µg/kg [ 26 ] and 7.0–7.1 µg/kg [ 28 ] in spices and herbs, respectively. A study conducted in Italy also showed a higher OTA concentration in spices, with a mean of 6.18 µg/kg [ 50 ].…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations